Bruxism, temporomandibular dysfunction and cervical impairments in females – Results from an observational study. (February 2020) - Piekartz, Harry von; Rösner, Charlotte; Batz, Angelina; Hall, Toby; Ballenberger, Nicolaus
Abstract: Purpose: Bruxism is highly prevalent and defined as abnormal habitual mouth activity including clenching of the teeth and increased jaw muscle activity. The association between bruxism and temporomandibular dysfunction (TMD) is debated, in particular the association between cervical spine impairments, bruxism, and TMD. Hence the purpose of this study was to identify the relationship between bruxism, TMD, and cervical spine impairments. Methods: This observational study categorized 55 female volunteers suitable for evaluation to a bruxism (n = 33) or non-bruxism group (n = 22) based on comprehensive screening using questionnaires and visual observation of the mouth by 2 independent dentists. Following this, both groups were evaluated for TMD, severity and location of head/neck pain, neck disability index (NDI), cervical spine impairments, and tissue mechanosensitivity. Regression analysis was used to evaluate the relationship between bruxism, TMD severity, and cervical impairments. Results: Coefficients of pain and bruxism were significantly associated with NDI scores (0.43, p < 0.001; 3.24, p = 0.01) with large and medium sized effects. As a consequence, both severity of TMD and bruxism status are independently associated with cervical impairments. Having TMD is an independent predictor for head/neck pain and cervical impairments. Pain associated with movement tests and tissue mechanosensitivity was found to be an important factor in bruxism. Conclusion: Clinicians need to be aware that signs of cervical movement impairment are not likely to be associated with bruxism, rather they should focus on improving orofacial function and tissue mechanosensitivity. Highlights: Bruxism is significantly associated with neck disability with medium sized effect. TMD is an independent predictor for head/neck pain and cervical dysfunction. Pain associated with movement tests and tissue sensitivity are factors in bruxism. Cervical tests of pain and not ROM impairment are important in bruxism.